Rhipicephalus sanguineus Infestation with Ehrlichiosis in Shitzu-Pomeranian Crossbred Dogs Treated using Red Fermented Rice: A Case Report - Diana, Kadek Leni Martha; Jayanti, Putu Devi; Batan, I Wayan (Universitas Airlangga, 2023)
This report aimed to provide information on the diagnosis, treatment, and therapeutic evaluation of Ehrlichiosis in crossbreed dogs treated using red fermented rice. A Shitzu-Pomeranian crossbreed was indicated with decreased appetite, weight loss, and the presence of high levels of pruritus due to suffering from blood parasites. Physical examination showed an infestation of Rhipicephalus sanguineus around the eyes and back area. A complete hematological examination and blood smear showed leukocytosis, lymphocytosis, thrombocytopenia, increased granulocytes, and the presence of intracytoplasmic bodies in monocytes. The results of the examination using the test kit showed that the sample was positive for Ehrlichiosis. Treatment using Doxycycline (5 mg/kg BW, for 28 days), Ivermectin 1% (0,2 ml SC), Diphenhydramine HCl 10 mg/kg (1,1 ml IM), Chlorpheniramine maleate (1 tablet/day for 14 days), Vitamin B12 (1 tablet/day for 28 days), and 5 ml of red fermented rice solution twice a day for 21 days. After 21 days, the whole treatment reported the appetite returned to normal, reduced infestation of R. sanguineus, and reduced frequency of pruritus.